Sirolimus, tacrolimus and low-dose methotrexate based graft-versus-host disease prophylaxis after non-ablative or reduced intensity conditioning in related and unrelated donor allogeneic hematopoietic cell transplant. Issue 3 (March 2015) - Ceberio, Izaskun; Devlin, Sean M.; Sauter, Craig; Barker, Juliet N.; Castro-Malaspina, Hugo; Giralt, Sergio; Ponce, Doris M.; Lechner, Lauren; Maloy, Molly A.; Goldberg, Jenna D.; Perales, Miguel-Angel
Abstract: Encouraging results have been reported with sirolimus, tacrolimus and low-dose methotrexate after non-myeloablative allogeneic hematopoietic cell transplant. We conducted a retrospective analysis of 71 patients with lymphoid malignancies treated with this prophylaxis regimen after non-myeloablative or reduced intensity allogeneic hematopoietic cell transplant. Grafts were human leukocyte antigen (HLA)-matched related in 29 (41%), matched unrelated in 36 (51%) and 9/10 HLA-matched unrelated in six (8%) patients. The regimen was well tolerated and over 90% of patients completed the planned treatment. The cumulative incidences of 1-year grade B–D and C–D acute graft-versus-host disease (GVHD) were 0.28 (95% confidence interval [CI], 0.18–0.39) and 0.07 (95% CI, 0.03–0.15), respectively, and of 1- and 2-year chronic GVHD (National Institutes of Health criteria) in 70 evaluable patients were 0.15 (95% CI, 0.08–0.24) and 0.33 (95% CI, 0.22–0.44), respectively. The median day of onset of acute GVHD was 123 days (range, 17–268 days). Peri-transplant rituximab or anti-thymocyte globulin did not affect GVHD. The cumulative incidence of 1-year non-relapse mortality and relapse were 4% and 20%, respectively. With a median follow-up of 3.5 (range: 0.18–5.1) years, overall survival and progression-free survival at 2 years were 82% and 66%, respectively. This GVHD regimen results in a low incidence and severity of acute and chronic GVHD after reduced intensity and non-myeloablative allogeneic hematopoietic cell transplant for lymphoid malignancies. The study also highlights the incidence of late onset acute GVHD in non-myeloablative/reduced intensity conditioning, and the contribution of the new GVHD staging system that more accurately reflects clinical outcomes.